The Application of Nanoparticle-Based Drug Delivery Systems in Checkpoint Blockade Cancer Immunotherapy - Huan Zhao; Yuanqi Li; Dan Wei; Hongrong Luo (Journal of Immunology Research)
Tumor is the most serious threat to human beings. Although war against cancer has been launched over forty years, cancer treatment is still far away from being satisfactory. Immunotherapy, especially checkpoint blockade immunotherapy, is a rising star that shows a promising future. To fulfill the requirement of depleting primary tumor and inhibiting tumor metastasis and recurrence, many researchers combined checkpoint blockade immunotherapy with other treatment strategies to extend the treatment outcome. Photodynamic therapy could induce immunogenic cell death, and checkpoint blockade could further accelerate the immunity; therefore, combining these two strategies publishes many papers. Additionally, photothermal therapy and immunotherapy were also utilized for combining with checkpoint blockade, which were also reviewed in this paper. Furthermore, antibodies, siRNA, and small molecule inhibitors are developed to block the checkpoint; therefore, we categorized the papers into three sections, combination nanoparticles with checkpoint blockade antibody, combination nanoparticles with checkpoint blockade siRNA, and combination nanoparticles with small molecule checkpoint inhibitors, and related researches were summarized. In conclusion, the combination nanoparticle with checkpoint blockade cancer immunity is a promising direction that may fulfill the requirement of cancer treatment.